Arabic dialectology: methodology and field research - Arnold, Werner (Harrassowitz Verlag, 2019)
Intro -- Contents -- Preface -- List of Charts, Figures and Tables -- List of Abbreviations and Symbols -- List of Contributors -- Field Research: Practical Experience -- Peter Behnstedt: The Research-Permit or: faydítu ʾē? -- Werner Arnold: Fieldwork in Germany -- Maciej Klimiuk and Maria Lipnicka: Dialectology in Practice: Notes from Fieldwork in Gozo -- Emilie Zuniga: Ethical and Social Aspects of Fieldwork in Arabic-Speaking Societies -- Judith Rosenhouse: Fieldwork and the Study of Spontaneous Colloquial Arabic Speech -- Thomas Leddy-Cecere: Fieldwork among Transnational Populations -- Aharon Geva-Kleinberger: From the Far East to the Middle East: Preserving Heritage throughDialectal Fieldwork -- Janet C.E. Watson, Miranda J. Morris, Abdullah al-Mahri,Munira A. al-Azraqi, Saeed al-Mahri and Ali al-Mahri: Modern South Arabian: Conducting Fieldwork in Dhofar, Mahrahand Eastern Saudi Arabia -- Tools, Methods and Historical Sources -- Assaf Bar-Moshe: Phonetic Analysis as a Supportive Tool for Phonemic Understanding:Two Case Studies from the Jewish Dialect of Baghdad -- Stefano Manfredi and Suat Istanbullu: A Multilayered and Data-Driven Method for Exploring Arabicin Multilingual Settings -- Jonathan Owens: Dialectology and the Quantitative Treatment of Discourse -- Jason Schroepfer: Some Tools for Fieldwork in Arabic Dialectology -- Liesbeth Zack: Historical Arabic Dialectology: Interpreting the Sources -- Samples of Questionnaires -- Peter Behnstedt, edited and translated by Maciej Klimiuk: Questionnaire for Syria -- Peter Behnstedt, edited by Maciej Klimiuk: Questionnaire for Morocco -- Peter Behnstedt and Manfred Woidich, edited by Maciej Klimiuk: Questionnaire for the Wortatlas der arabischen Dialekte -- Index of Names -- Index of Places -- Index of Subjects and Languages.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Dialektologie; Arabisch; Feldforschung; Dialektgeografie